High-oxidation-resistance composite copper paste and preparation method thereof

By using high oxidation resistance composite copper slurry, the metallization problem of photovoltaic cell cells caused by the oxidation of nano copper slurry is solved, and an efficient and low-cost metallization process is achieved, forming a metallization gate line with high conductivity and low porosity.

CN119852002APending Publication Date: 2025-04-18YOUYANNA MICRO NEW MATERIALS (BEIJING) CO LTD

Patent Information

Application Number
CN202411953827.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Nanocopper paste is easily oxidized during storage and use, resulting in high porosity, low conductivity, and complex process formed in the metallization process of photovoltaic cells.

Method used

A high-oxidation resistance composite copper slurry is used, which consists of nanosilver powder, nanocopper powder, submicron copper powder, microcopper powder, microtin-based alloy powder and organic carrier. Through grinding and dispersion and heat curing, a dense metallized gate line is formed.

Benefits of technology

The gate lines are low porosity, high density and high conductivity, and the process flow is simplified, so that efficient metallization can be achieved without pressurization, protective atmosphere or vacuum conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852002A_ABST
    Figure CN119852002A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of slurry for heterojunction photovoltaic cell grid metallization, and particularly relates to high-oxidation-resistance composite copper slurry and a preparation method thereof, and the high-oxidation-resistance composite copper slurry is formed by mixing the following raw materials: first conductive metal powder, second conductive metal powder, micron tin-based alloy powder and an organic carrier; the first conductive metal powder is selected from at least one of nano silver powder and nano copper powder; the second conductive metal powder is selected from at least one of submicron copper powder and micron copper powder; the organic vehicle comprises a solvent, an active agent and a thermosetting resin. The high-oxidation-resistance composite copper paste provided by the invention can solve the problem of oxidation of the nano copper powder in a grid line metallization process, so that the finally formed grid line is low in porosity, high in density and high in conductivity, the flow is short, the process is simple, and grid line metallization is realized without pressurization, protective atmosphere and vacuum conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slurry for grid metallization of heterojunction photovoltaic cells, and specifically relates to a highly anti-oxidative composite copper slurry and a preparation method thereof. Background Art

[0002] Nano silver paste or nano copper paste is mainly used in the manufacturing of metal electrode grid lines of low-temperature process high-efficiency photovoltaic cell modules such as HJT heterojunction cells, HBC cells, and perovskite stacked cells. Driven by the current trend of cost reduction, pure nano silver paste is gradually replaced by base metal pastes such as nano copper paste and silver-coated copper paste.

[0003] However, silver-coated copper paste still requires a certain proportion of metallic silver. The industry has been committed to reducing the silver content, but reducing the silver content brings problems such as uneven coating and easy oxidation of exposed copper powder. In addition, the coating process is complicated and there are many process links. Therefore, silver-coated copper paste is considered to be a transition at this stage. The use of nano-copper paste has the problem that nano-copper powder is difficult to store and easy to oxidize. In addition, during the metallization process of photovoltaic cells, the nano-copper powder will undergo further oxidation and cannot form a dense sintered layer, resulting in the final metallized grid lines having high porosity and low conductivity. Therefore, solving the oxidation problem of nano-copper paste during storage and use has always been a technical difficulty that the industry is concerned about. Summary of the invention

[0004] The main purpose of the present invention is to propose a highly antioxidant composite copper paste and a preparation method thereof. The highly antioxidant composite copper paste provided by the present invention can solve the problem of nano-copper powder oxidation during gate line metallization, so that the final gate line has low porosity, high density, and high conductivity, and has a short process and a simple process. Gate line metallization can be achieved without pressurization, protective atmosphere, or vacuum conditions.

[0005] A first aspect of the present invention provides a highly antioxidant composite copper paste, which is formed by mixing the following raw materials: a first conductive metal powder, a second conductive metal powder, a micron tin-based alloy powder and an organic carrier; wherein the first conductive metal powder is selected from at least one of nano silver powder and nano copper powder; the second conductive metal powder is selected from at least one of submicron copper powder and micron copper powder; and the organic carrier contains a solvent, an activator and a thermosetting resin.

[0006] In some embodiments of the present invention, the particle size of the first conductive metal powder is 50 nm to 100 nm.

[0007] In some embodiments of the present invention, the particle size of the second conductive metal powder is 100 nm to 1 μm, and the shape of the second conductive metal powder includes at least one of flake, spherical, and dendritic.

[0008] In some embodiments of the present invention, the particle size of the micron tin-based alloy powder is 2 μm to 15 μm.

[0009] In some embodiments of the present invention, the micron tin-based alloy powder is selected from one or more of tin-lead alloy powder, tin-lead-silver alloy powder, tin-lead-bismuth alloy powder, tin-copper alloy powder, tin-silver alloy powder, tin-silver-copper alloy powder, tin-bismuth alloy powder, tin-bismuth-silver alloy powder, and tin-antimony alloy powder.

[0010] In some embodiments of the present invention, based on the total weight of all raw materials being 100%, the mass of the first conductive metal powder accounts for 10% to 20%, the mass of the second conductive metal powder accounts for 60% to 80%, the mass of the micron tin-based alloy powder accounts for 1% to 10%, and the mass of the organic carrier accounts for 10% to 20%.

[0011] In some embodiments of the present invention, based on the total weight of the organic carrier being 100%, the mass percentage of the active agent is 3% to 5%; and the mass percentage of the thermosetting resin is 25% to 55.5%.

[0012] In some embodiments of the present invention, the thermosetting resin is selected from one or more of epoxy resin, polyamide resin, saturated polyester resin, polyurethane resin, acrylic resin, and silicone resin.

[0013] In some embodiments of the present invention, the active agent is selected from one or more of citric acid, dibromosuccinic acid, stearic acid, succinic acid, salicylic acid, malonic acid, oxalic acid, glutaric acid, adipic acid, pimelic acid, azelaic acid, and sebacic acid.

[0014] In some embodiments of the present invention, the solvent is selected from one or more of octyl ether, tetrahydrofurfuryl alcohol, MPEG-250, MPEG-400, ethylene glycol methyl ether, ethylene glycol ethyl ether, polyethylene glycol 400, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, 2,2,4-trimethyl 1,3-pentanediol diisobutyrate, and butyl acetate.

[0015] In some embodiments of the present invention, the organic vehicle further comprises at least one of a curing agent, a surfactant, a dispersant and a thixotropic agent.

[0016] In some embodiments of the present invention, the curing agent is selected from at least one of organic amines and their derivatives, or selected from at least one of imidazoles and their derivatives.

[0017] In some embodiments of the present invention, the surfactant is selected from one or more of quaternary ammonium oleate, ammonium fluoroalkyl carboxylate, and dimethylamine hydrochloride.

[0018] In some embodiments of the present invention, the thixotropic agent is selected from one or more of castor oil, hydrogenated castor oil, and hardened castor oil.

[0019] In some embodiments of the present invention, the dispersant is selected from at least one of oleic acid, dodecyl mercaptan, sodium dodecyl sulfonate, and tetradecyltrimethylammonium bromide.

[0020] In some embodiments of the present invention, based on the total weight of the organic carrier as 100%, the mass percentage of the curing agent is 5.5% to 20.5%; the mass percentage of the surfactant is 5% to 13%; the mass percentage of the dispersant is 3% to 7%; and the mass percentage of the thixotropic agent is 3% to 5%.

[0021] In some embodiments of the present invention, the curing temperature of the composite copper paste is 150° C. to 350° C., and the curing time is 5 min to 30 min.

[0022] The second aspect of the present invention provides a method for preparing the highly antioxidant composite copper paste described in the first aspect, the preparation method comprising: mixing a first conductive metal powder, a second conductive metal powder and an organic carrier, and adding micron tin-based alloy powder after sufficient grinding and dispersion, stirring evenly, to obtain the composite copper paste.

[0023] In some embodiments of the present invention, the stirring speed is 1 rpm to 100 rpm, and the stirring time is 10 min to 30 min.

[0024] In some embodiments of the present invention, the grinding is performed using a three-roll grinder, the roller spacing is 1 μm to 10 μm, and the number of grinding times is 3 to 5 times.

[0025] In some embodiments of the present invention, the preparation method further comprises evacuating the composite copper slurry in a closed environment to remove bubbles inside the slurry.

[0026] In some embodiments of the present invention, the vacuum degree of the vacuum pumping is 10 -1 Pa~10 -5 Pa.

[0027] The composite copper paste of the present invention uses conductive metal powders of different particle sizes, micron tin-based alloy powders and organic carriers as raw materials. During the heating and curing process of the composite copper paste, nano-scale powders will form sintering active sites, forming sintering connections between submicron and / or micron copper powders, and the submicron and / or micron copper powders serve as skeleton supports; the active ingredients in the organic carrier can remove the oxide layer of the copper powder and improve the sintering activity of the copper powder, while the resin component in the carrier can prevent the copper powder from further oxidation. After the micron tin alloy powder in the composite copper paste is melted, it will fully infiltrate the gaps between the copper powders under the action of the small size effect and the siphon effect, and the copper powder will be wrapped in the tin alloy melt, forming a composite material grid line with the tin alloy as a protective layer and copper as a matrix conductive channel, and the grid line has low porosity, high density and excellent conductivity.

[0028] The composite copper paste of the present invention is used for grid metallization of high-efficiency heterojunction photovoltaic cells and has the advantages of low porosity, high density and high conductivity.

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0031] Figure 1 This is a microscopic photograph of the metallized grid lines of a photovoltaic cell formed using the highly anti-oxidative composite copper paste obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0034] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0035] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0036] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.

[0037] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0038] In the description of the embodiments of the present invention, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present invention.

[0039] In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.

[0040] Although there are technical solutions for improving density and conductivity in the existing technology, they mostly require specific devices and pressurization processes to improve density and conductivity, and cannot meet the needs of photovoltaic cell grid metallization. This is because photovoltaic cells are relatively brittle and easily broken under pressurized conditions.

[0041] It is worth mentioning that the preparation process of nano copper powder and ultrafine tin alloy powder of 5 microns and below is already a mature process, and the powder raw materials are easily available.

[0042] The highly antioxidant composite copper paste provided by the present invention is formed by mixing the following raw materials: a first conductive metal powder, a second conductive metal powder, a micron tin-based alloy powder and an organic carrier; wherein the first conductive metal powder is selected from at least one of nano silver powder and nano copper powder; the second conductive metal powder is selected from at least one of submicron copper powder and micron copper powder; and the organic carrier comprises a solvent, an activator and a thermosetting resin.

[0043] In an embodiment of the present invention, the composite copper paste uses conductive metal powders of different particle sizes, micron tin-based alloy powders and organic carriers as raw materials. During the heating and curing process of the composite copper paste, nano-scale powders will form sintering active sites, and sintering connections will be formed between submicron and / or micron copper powders, with submicron and / or micron copper powders serving as skeleton supports; the active ingredients in the organic carrier can remove the oxide layer of the copper powder and improve the sintering activity of the copper powder, while the resin component in the carrier can prevent the copper powder from further oxidation. After the micron tin alloy powder in the composite copper paste is melted, it will fully wet the gaps between the copper powders under the action of the small size effect and the siphon effect, and the copper powder will be wrapped in the tin alloy melt, forming a composite material grid line with the tin alloy as a protective layer and copper as a conductive channel of the matrix, and the grid line has low porosity, high density and excellent conductivity.

[0044] In the raw material composition of the high oxidation resistance composite copper paste provided by the present invention, based on the total weight of all raw materials as 100%, the mass proportion of the first conductive metal powder is 10% to 20%, the mass proportion of the second conductive metal powder is 60% to 80%, the mass proportion of the micron tin-based alloy powder is 1% to 10%, and the mass proportion of the organic carrier is 10% to 20%.

[0045] In an embodiment of the present invention, the weight percentage of the first conductive metal powder can be one of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any value that meets the above range. The weight percentage of the second conductive metal powder can be one of 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, or any value that meets the above range. The weight percentage of the micron tin-based alloy powder can be one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value that meets the above range. The weight percentage of the organic carrier can be one of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value within the above range.

[0046] In an embodiment of the present invention, the particle size of the first conductive metal powder is 50 nm to 100 nm. For example, the particle size of the first conductive metal powder can be one of 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value within the above range.

[0047] In some embodiments of the present invention, the particle size of the nano silver powder is 50 nm to 100 nm. For example, the particle size of the nano silver powder can be one of 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value satisfying the above range.

[0048] In some embodiments of the present invention, the particle size of the nano copper powder is 50 nm to 100 nm. For example, the particle size of the nano copper powder can be one of 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value satisfying the above range.

[0049] In an embodiment of the present invention, the particle size of the second conductive metal powder is 100 nm to 1 μm. For example, the particle size of the second conductive metal powder can be one of 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or any value within the above range.

[0050] In some embodiments of the present invention, the particle size of the submicron copper powder is 100 nm to 1 μm. For example, the particle size of the submicron copper powder can be one of 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or any value within the above range.

[0051] In some embodiments of the present invention, the particle size of the micron copper powder is 100 nm to 1 μm. For example, the particle size of the micron copper powder can be one of 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or any value within the above range.

[0052] In some embodiments of the present invention, the second conductive metal powder has a shape of at least one of flake, spherical, and dendritic.

[0053] In an embodiment of the present invention, the particle size of the micron tin-based alloy powder is 2 μm to 15 μm. For example, the particle size of the micron tin-based alloy powder can be one of 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any value that satisfies the above range.

[0054] In an embodiment of the present invention, the micron tin-based alloy powder is selected from one or more of tin-lead alloy powder, tin-lead-silver alloy powder, tin-lead-bismuth alloy powder, tin-copper alloy powder, tin-silver alloy powder, tin-silver-copper alloy powder, tin-bismuth alloy powder, tin-bismuth-silver alloy powder, and tin-antimony alloy powder.

[0055] In an embodiment of the present invention, based on the total weight of the organic carrier as 100%, the weight of the thermosetting resin accounts for 25% to 55.5%. Exemplarily, the weight of the thermosetting resin may be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 55.5% or any value satisfying the above range.

[0056] In some embodiments of the present invention, the thermosetting resin is selected from one or more of epoxy resin, polyamide resin, saturated polyester resin, polyurethane resin, acrylic resin, and silicone resin.

[0057] In an embodiment of the present invention, the mass proportion of the active agent is 3% to 5% based on the total weight of the organic carrier as 100%. For example, the mass proportion of the active agent can be 3%, 4%, 5% or any value satisfying the above range.

[0058] In some embodiments of the present invention, the active agent is selected from one or more of citric acid, dibromosuccinic acid, stearic acid, succinic acid, salicylic acid, malonic acid, oxalic acid, glutaric acid, adipic acid, pimelic acid, azelaic acid, and sebacic acid.

[0059] In an embodiment of the present invention, the weight of the solvent is 10% to 30% based on the total weight of the organic carrier as 100%. For example, the weight of the solvent may be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or any value satisfying the above range.

[0060] In some embodiments of the present invention, the solvent is selected from one or more of octyl ether, tetrahydrofurfuryl alcohol, MPEG-250, MPEG-400, ethylene glycol methyl ether, ethylene glycol ethyl ether, polyethylene glycol 400, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, pinene alcohol, 2,2,4-trimethyl 1,3-pentanediol diisobutyrate, and butyl acetate.

[0061] In an embodiment of the present invention, the organic vehicle further includes at least one of a curing agent, a surfactant, a dispersant and a thixotropic agent.

[0062] In an embodiment of the present invention, based on the total weight of the organic carrier as 100%, the mass proportion of the curing agent is 5.5% to 20.5%. Exemplarily, the mass proportion of the curing agent can be 5.5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 20.5% or any value satisfying the above range.

[0063] In some embodiments of the present invention, the curing agent is selected from at least one of organic amines and their derivatives, including PA66, PA610, PA1010, PA1212, ethylenediamine, distearylamine, laurylamine, etc., or is selected from at least one of imidazoles and their derivatives, including 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, etc.

[0064] In an embodiment of the present invention, the mass proportion of the surfactant is 5% to 13% based on the total weight of the organic carrier as 100%. For example, the mass proportion of the surfactant can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13% or any value satisfying the above range.

[0065] In some embodiments of the present invention, the surfactant is selected from one or more of quaternary ammonium oleate, ammonium fluoroalkyl carboxylate, and dimethylamine hydrochloride.

[0066] In an embodiment of the present invention, the mass proportion of the thixotropic agent is 3% to 5% based on the total weight of the organic carrier as 100%. For example, the mass proportion of the thixotropic agent can be 3%, 4%, 5% or any value within the above range.

[0067] In some embodiments of the present invention, the thixotropic agent is selected from one or more of castor oil, hydrogenated castor oil, and hardened castor oil.

[0068] In an embodiment of the present invention, the mass proportion of the dispersant is 3% to 7% based on the total weight of the organic carrier as 100%. For example, the mass proportion of the dispersant can be one of 3%, 4%, 5%, 6%, 7% or any value satisfying the above range.

[0069] In some embodiments of the present invention, the dispersant is selected from at least one of oleic acid, dodecyl mercaptan, sodium dodecyl sulfonate, and tetradecyl trimethyl ammonium bromide.

[0070] In an embodiment of the present invention, the curing temperature of the composite copper paste is 150°C to 350°C, and the curing time is 5min to 30min. Exemplarily, the curing temperature of the composite copper paste can be one of 150°C, 200°C, 250°C, 300°C, 350°C, or any value satisfying the above range. The curing time of the composite copper paste can be one of 5min, 10min, 15min, 20min, 25min, 30min, or any value satisfying the above range.

[0071] The present invention also provides a method for preparing the above-mentioned highly antioxidant composite copper paste. The key to the preparation method is to mix the first conductive metal powder, the second conductive metal powder and the organic carrier, and add micron tin-based alloy powder after sufficient grinding and dispersion, and stir evenly to obtain the composite copper paste.

[0072] The method for preparing the highly anti-oxidative composite copper slurry provided by the present invention is specifically carried out according to the following steps.

[0073] (1) Preparation of organic carrier.

[0074] In an embodiment of the present invention, the components forming the organic vehicle are mixed and stirred uniformly to obtain the organic vehicle.

[0075] In an embodiment of the present invention, the speed of mixing and stirring is 1 rpm to 100 rpm, and the stirring time is 10 min to 30 min. Exemplarily, the speed of mixing and stirring can be 1 rpm, 5 rpm, 10 rpm, 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm or any numerical value satisfying the above range value. The stirring time can be 10 min, 12 min, 14 min, 15 min, 16 min, 18 min, 20 min, 22 min, 24 min, 25 min, 26 min, 28 min, 30 min or any numerical value satisfying the above range value.

[0076] In some embodiments of the present invention, the components forming the organic carrier are weighed in proportion, added into a stirring kettle, and stirred thoroughly at a stirring speed of 1 rpm to 100 rpm for 10 min to 30 min. After mixing evenly, an organic carrier is obtained.

[0077] (2) Evenly mixing nano silver powder and / or nano copper powder, submicron copper powder and / or micron copper powder with an organic carrier, and grinding and dispersing the obtained mixed slurry to obtain a slurry to be used.

[0078] In an embodiment of the present invention, a three-roll mill is used for grinding and dispersion. During grinding, the roller spacing of the three-roll mill is 1 μm to 10 μm, and the number of grindings is 3 to 5 times. For example, the roller spacing can be one of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any value that satisfies the above range. The number of grindings can be 3 times, 4 times, or 5 times, which can be set according to actual needs.

[0079] In some embodiments of the present invention, nano silver powder and / or nano copper powder, submicron copper powder and / or micron copper powder are added to a stirring kettle and fully stirred at a stirring speed of 1 rpm to 100 rpm for 10 min to 30 min to mix evenly with the organic carrier to obtain a mixed slurry, and then the mixed slurry is fully ground and dispersed with a three-roll grinder to obtain a slurry for use.

[0080] In an embodiment of the present invention, the stirring speed of the conductive metal powder and the organic carrier can be 1 rpm, 5 rpm, 10 rpm, 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm, or any value satisfying the above range. The stirring time can be 10 min, 12 min, 14 min, 15 min, 16 min, 18 min, 20 min, 22 min, 24 min, 25 min, 26 min, 28 min, 30 min, or any value satisfying the above range.

[0081] (3) Add micron-sized tin-based alloy powder to the standby slurry obtained in step (2) under uniform stirring, and stir well to obtain a composite copper slurry.

[0082] In an embodiment of the present invention, the speed of uniform stirring is 1 rpm to 100 rpm. Exemplarily, the stirring speed can be 1 rpm, 5 rpm, 10 rpm, 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm or any value satisfying the above range.

[0083] In an embodiment of the present invention, the stand-by slurry obtained in step (2) is placed in a stirring kettle, and under uniform stirring conditions, the rotation speed is 1 rpm to 100 rpm, micron-grade tin-based alloy powder is added, and stirred evenly, such as for a stirring time of 10 min to 30 min, to obtain a composite copper slurry.

[0084] (4) The stirring kettle is sealed and the inside of the kettle is evacuated under the condition of uniform stirring, so that the bubbles inside the composite copper slurry are fully removed while the composite copper slurry is being stirred.

[0085] In the embodiment of the present invention, the vacuum degree of the vacuum pump is 10 -1 Pa~10 -5 Pa. For example, the vacuum degree can be 10 -1 Pa, 10 -2 Pa, 10 -3 Pa, 10 -4 Pa, 10 -5 Pa or any value that satisfies the above range.

[0086] In an embodiment of the present invention, the uniform stirring speed of the stirring kettle is 1 rpm to 100 rpm. For example, the stirring speed can be 1 rpm, 5 rpm, 10 rpm, 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm or any value satisfying the above range.

[0087] (5) Stop stirring, release the pressure, open the stirring kettle, and take out the final finished composite copper slurry.

[0088] The composite copper paste of the present invention is used for grid metallization of heterojunction photovoltaic cell sheets.

[0089] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0090] Example 1

[0091] A highly anti-oxidative composite copper paste is formed by mixing the following raw materials: nano copper powder, nano silver powder, submicron copper powder, micron copper powder, organic carrier and micron tin alloy powder. Among them, based on the total weight of all raw materials as 100%, the particle size of the nano copper powder is 80nm, and the mass proportion is 5%wt; the particle size of the nano silver powder is 100nm, and the mass proportion is 5%wt; the particle size of the submicron copper powder is 800nm, and the mass proportion is 40%wt; the particle size of the micron copper powder is 1μm, and the mass proportion is 30%wt; the micron tin alloy powder adopts Sn64Bi35Ag1 alloy powder, with a particle size of 5μm and a mass proportion of 8.5%; the mass proportion of the organic carrier is 11.5%wt, and the organic carrier contains MPEG-250, acrylic resin, stearic acid, fluoroalkyl carboxylic acid ammonium salt, and hydrogenated castor oil. Based on the weight of the organic carrier being 100%, the mass of MPEG-250 accounts for 57%, the mass of acrylic resin accounts for 30%, the mass of stearic acid accounts for 5%, the mass of fluoroalkyl carboxylic acid ammonium salt accounts for 5%, and the mass of hydrogenated castor oil accounts for 3%.

[0092] The preparation method of the highly anti-oxidative composite copper paste is as follows:

[0093] (1) MPEG-250, acrylic resin, stearic acid, fluoroalkyl carboxylic acid ammonium salt and hydrogenated castor oil are added to a stirring kettle and stirred thoroughly at a stirring speed of 10 rpm for 20 min. After mixing evenly, an organic carrier is obtained.

[0094] (2) Add nano copper powder, nano silver powder, submicron copper powder, and micron copper powder into a stirring kettle and stir them thoroughly at a stirring speed of 10 rpm for 20 min to mix them evenly with the organic carrier to obtain a mixed slurry. Then, the mixed slurry is fully ground and dispersed using a three-roll grinder with a roller spacing of 5 μm and a grinding number of 5 times to obtain a slurry for use.

[0095] (3) The above-mentioned slurry to be used is placed in a stirring kettle, and under the condition of uniform stirring at a stirring speed of 10 rpm, Sn64Bi35Ag1 alloy powder is evenly added and fully stirred to obtain a composite copper slurry.

[0096] (4) The stirred kettle was sealed and the stirring speed was 10 rpm under the condition of uniform stirring. The inside of the kettle was evacuated to a vacuum degree of 10 -5 Pa, so that the composite copper slurry is stirred and the bubbles inside the slurry are fully eliminated.

[0097] (5) Stop stirring, release the pressure, open the stirring kettle, and take out the finished composite copper slurry.

[0098] The composite copper paste prepared in Example 1 is applied to the surface of the HJT heterojunction cell by screen printing to form an electrode to be cured on the front side of the cell; wherein the printed paste has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 195°C for 5 min in air to cure the paste and form a metallized grid line.

[0099] Example 2

[0100] A highly antioxidant composite copper paste is formed by mixing the following raw materials: nano copper powder, submicron copper powder, micron copper powder, organic carrier and micron tin alloy powder. Among them, based on the total weight of all raw materials as 100%, the particle size of the nano copper powder is 100nm, and the mass proportion is 10%wt; the particle size of the submicron copper powder is 800nm, and the mass proportion is 40%wt; the particle size of the micron copper powder is 1μm, and the mass proportion is 25%wt; the micron tin alloy powder uses Sn43Pb43Bi14 alloy powder, with a particle size of 8μm and a mass proportion of 14.5%; the mass proportion of the organic carrier is 10.5%wt, and the organic carrier contains ethylene glycol methyl ether, polyurethane resin, glutaric acid, dimethylamine hydrochloride, and hydrogenated castor oil. Based on the weight of the organic carrier being 100%, the mass of ethylene glycol methyl ether accounts for 53%, the mass of the polyurethane resin accounts for 30%, the mass of glutaric acid accounts for 5%, the mass of dimethylamine hydrochloride accounts for 7%, and the mass of hydrogenated castor oil accounts for 5%.

[0101] The preparation method of the highly anti-oxidative composite copper paste is as follows:

[0102] (1) Ethylene glycol methyl ether, polyurethane resin, glutaric acid, dimethylamine hydrochloride and hydrogenated castor oil are added to a stirring kettle and stirred thoroughly at a stirring speed of 20 rpm for 10 min. After mixing evenly, an organic carrier is obtained.

[0103] (2) Add nano copper powder, submicron copper powder and micron copper powder into a stirring kettle and stir them thoroughly at a stirring speed of 20 rpm for 20 min to mix them evenly with the organic carrier to obtain a mixed slurry. Then, the mixed slurry is fully ground and dispersed using a three-roll grinder with a roller spacing of 5 μm and a grinding number of 5 times to obtain a slurry for use.

[0104] (3) The above-mentioned slurry to be used is placed in a stirring kettle, and under the condition of uniform stirring at a stirring speed of 20 rpm, Sn43Pb43Bi14 alloy powder is evenly added and fully stirred to obtain a composite copper slurry.

[0105] (4) The stirred kettle was sealed and the stirring speed was 20 rpm under the condition of uniform stirring. The vacuum degree of the kettle was 10 -2 Pa, so that the composite copper slurry is stirred and the bubbles inside the slurry are fully eliminated.

[0106] (5) Stop stirring, release the pressure, open the stirring kettle, and take out the finished composite copper slurry.

[0107] The composite copper paste prepared in Example 2 is applied to the surface of the HJT heterojunction cell by screen printing to form an electrode to be cured on the front side of the cell; wherein the printed paste has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 250°C for 5 min in air to cure the paste and form a metallized grid line.

[0108] Example 3

[0109] A highly antioxidant composite copper paste is formed by mixing the following raw materials: nano silver powder, micron copper powder, organic carrier and micron tin alloy powder. Among them, based on the total weight of all raw materials as 100%, the particle size of the nano silver powder is 100nm, and the mass proportion is 8%wt; the particle size of the micron copper powder is 800nm, and the mass proportion is 70%wt; the micron tin alloy powder uses Sn63Pb37 alloy powder, the particle size is 10μm, and the mass proportion is 12%wt; the mass proportion of the organic carrier is 10%wt, and the organic carrier contains tetrahydrofurfuryl alcohol, saturated polyester resin, dibromosuccinic acid, oleic acid quaternary ammonium salt, and castor oil. Based on the weight of the organic carrier as 100%, the mass proportion of tetrahydrofurfuryl alcohol is 52%, the mass proportion of the saturated polyester resin is 32%, the mass proportion of dibromosuccinic acid is 4%, the mass proportion of oleic acid quaternary ammonium salt is 8%, and the mass proportion of castor oil is 4%.

[0110] The preparation method of the highly anti-oxidative composite copper paste is as follows:

[0111] (1) Tetrahydrofurfuryl alcohol, saturated polyester resin, dibromosuccinic acid, oleic acid quaternary ammonium salt and castor oil are added to a stirring kettle and stirred thoroughly at a stirring speed of 30 rpm for 10 min. After mixing evenly, an organic carrier is obtained.

[0112] (2) Add nano silver powder and micron copper powder into a stirring kettle and stir them thoroughly at a stirring speed of 30 rpm for 20 min to mix them evenly with the organic carrier to obtain a mixed slurry. Then, the mixed slurry is fully ground and dispersed using a three-roll mill with a roller spacing of 5 μm and a grinding number of 5 times to obtain a slurry for use.

[0113] (3) The above-mentioned slurry to be used is placed in a stirring kettle, and under the condition of uniform stirring at a stirring speed of 30 rpm, Sn63Pb37 alloy powder is evenly added and fully stirred to obtain a composite copper slurry.

[0114] (4) The stirred kettle was sealed and the stirring speed was 30 rpm under the condition of uniform stirring. The vacuum degree of the kettle was 10 -1 Pa, so that the composite copper slurry is stirred and the bubbles inside the slurry are fully eliminated.

[0115] (5) Stop stirring, release the pressure, open the stirring kettle, and take out the finished composite copper slurry.

[0116] The composite copper paste prepared in Example 3 is applied to the surface of the HJT heterojunction cell by screen printing to form an electrode to be cured on the front side of the cell; wherein the printed paste has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 195°C for 5 min in air to cure the paste and form a metallized grid line.

[0117] Example 4

[0118] A highly antioxidant composite copper paste is formed by mixing the following raw materials: nano copper powder, micron copper powder, organic carrier and micron tin alloy powder. Among them, based on the total weight of all raw materials as 100%, the particle size of the nano copper powder is 80nm, and the mass proportion is 10%wt; the particle size of the micron copper powder is 1μm, and the mass proportion is 60%wt; the micron tin alloy powder uses Sn42Bi58 alloy powder, the particle size is 15μm, and the mass proportion is 20.5%; the mass proportion of the organic carrier is 9.5%wt, and the organic carrier contains polyethylene glycol 400, polyamide resin, adipic acid, oleic acid quaternary ammonium salt, and hardened castor oil. Based on the weight of the organic carrier as 100%, the mass proportion of polyethylene glycol 400 is 47.5%, the mass proportion of polyamide resin is 36%, the mass proportion of adipic acid is 4.2%, the mass proportion of oleic acid quaternary ammonium salt is 8.8%, and the mass proportion of hardened castor oil is 3.5%.

[0119] The preparation method of the highly anti-oxidative composite copper paste is as follows:

[0120] (1) Add polyethylene glycol 400, polyamide resin, adipic acid, oleic acid quaternary ammonium salt and hardened castor oil into a stirring kettle and stir them thoroughly at a stirring speed of 50 rpm for 10 min. After mixing evenly, an organic carrier is obtained.

[0121] (2) Add nano copper powder and micron copper powder into a stirring kettle and stir them thoroughly at a stirring speed of 50 rpm for 20 min to mix them evenly with the organic carrier to obtain a mixed slurry. Then, the mixed slurry is fully ground and dispersed using a three-roll grinder with a roller spacing of 5 μm and a grinding number of 5 times to obtain a slurry for use.

[0122] (3) The above-mentioned slurry to be used is placed in a stirring kettle, and under the condition of uniform stirring at a stirring speed of 50 rpm, Sn42Bi58 alloy powder is evenly added and fully stirred to obtain a composite copper slurry.

[0123] (4) The stirred kettle was sealed and the stirring speed was 50 rpm under the condition of uniform stirring. The vacuum degree of the kettle was 10 -3Pa, so that the composite copper slurry is stirred and the bubbles inside the slurry are fully eliminated.

[0124] (5) Stop stirring, release the pressure, open the stirring kettle, and take out the finished composite copper slurry.

[0125] The composite copper paste prepared in Example 4 is applied to the surface of the HJT heterojunction cell by screen printing to form an electrode to be cured on the front side of the cell; wherein the printed paste has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 250°C for 5 min in air to cure the paste and form a metallized grid line.

[0126] Example 5

[0127] A highly antioxidant composite copper paste is formed by mixing the following raw materials: nano copper powder, micron copper powder, organic carrier and micron tin alloy powder. Among them, based on the total weight of all raw materials as 100%, the particle size of the nano copper powder is 80nm, and the mass proportion is 10%wt; the particle size of the micron copper powder is 1μm, and the mass proportion is 60%wt; the micron tin alloy powder uses Sn42Bi58 alloy powder, the particle size is 15μm, and the mass proportion is 20.5%; the mass proportion of the organic carrier is 9.5%wt, and the organic carrier contains polyethylene glycol 400, polyamide resin, adipic acid, oleic acid quaternary ammonium salt, hardened castor oil, and ethylenediamine. Based on the weight of the organic carrier as 100%, the mass proportion of polyethylene glycol 400 is 51%, the mass proportion of polyamide resin is 30%, the mass proportion of adipic acid is 5%, the mass proportion of oleic acid quaternary ammonium salt is 5%, the mass proportion of hardened castor oil is 3%, and the mass proportion of ethylenediamine is 6%.

[0128] The preparation method of the highly anti-oxidative composite copper paste is as follows:

[0129] (1) Add polyethylene glycol 400, polyamide resin, adipic acid, oleic acid quaternary ammonium salt, hardened castor oil, and ethylenediamine into a stirring kettle and stir thoroughly at a stirring speed of 50 rpm for 10 min. After mixing evenly, an organic carrier is obtained.

[0130] (2) Add nano copper powder and micron copper powder into a stirring kettle and stir them thoroughly at a stirring speed of 50 rpm for 20 min to mix them evenly with the organic carrier to obtain a mixed slurry. Then, the mixed slurry is fully ground and dispersed using a three-roll grinder with a roller spacing of 5 μm and a grinding number of 5 times to obtain a slurry for use.

[0131] (3) The above-mentioned slurry to be used is placed in a stirring kettle, and under the condition of uniform stirring at a stirring speed of 50 rpm, Sn42Bi58 alloy powder is evenly added and fully stirred to obtain a composite copper slurry.

[0132] (4) The stirred kettle was sealed and the stirring speed was 50 rpm under the condition of uniform stirring. The vacuum degree of the kettle was 10 -3 Pa, so that the composite copper slurry is stirred and the bubbles inside the slurry are fully eliminated.

[0133] (5) Stop stirring, release the pressure, open the stirring kettle, and take out the finished composite copper slurry.

[0134] The composite copper paste prepared in Example 5 is applied to the surface of the HJT heterojunction cell by screen printing to form an electrode to be cured on the front side of the cell; wherein the printed paste has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 250°C for 5 min in air to cure the paste and form a metallized grid line.

[0135] Example 6

[0136] A highly antioxidant composite copper paste is formed by mixing the following raw materials: nano copper powder, micron copper powder, organic carrier and micron tin alloy powder. Based on the total weight of all raw materials as 100%, the particle size of the nano copper powder is 80nm, and the mass ratio is 10%wt; the particle size of the micron copper powder is 1μm, and the mass ratio is 60%wt; the micron tin alloy powder uses Sn42Bi58 alloy powder, the particle size is 15μm, and the mass ratio is 20.5%; the mass ratio of the organic carrier is 9.5%wt, and the organic carrier contains polyethylene glycol 400, polyamide resin, adipic acid, oleic acid quaternary ammonium salt, hardened castor oil, laurylamine, and dodecyl mercaptan. Based on the weight of the organic carrier as 100%, the mass of polyethylene glycol 400 accounts for 50%, the mass of polyamide resin accounts for 28%, the mass of adipic acid accounts for 5%, the mass of oleic acid quaternary ammonium salt accounts for 5%, the mass of hardened castor oil accounts for 3%, the mass of lauryl amine accounts for 6%, and the mass of dodecyl mercaptan accounts for 3%.

[0137] The preparation method of the highly anti-oxidative composite copper paste is as follows:

[0138] (1) Add polyethylene glycol 400, polyamide resin, adipic acid, oleic acid quaternary ammonium salt, hardened castor oil, lauryl amine and dodecyl mercaptan into a stirring kettle and stir them thoroughly at a stirring speed of 50 rpm for 10 min. After mixing evenly, an organic carrier is obtained.

[0139] (2) Add nano copper powder and micron copper powder into a stirring kettle and stir them thoroughly at a stirring speed of 50 rpm for 20 min to mix them evenly with the organic carrier to obtain a mixed slurry. Then, the mixed slurry is fully ground and dispersed using a three-roll grinder with a roller spacing of 5 μm and a grinding number of 5 times to obtain a slurry for use.

[0140] (3) The above-mentioned slurry to be used is placed in a stirring kettle, and under the condition of uniform stirring at a stirring speed of 50 rpm, Sn42Bi58 alloy powder is evenly added and fully stirred to obtain a composite copper slurry.

[0141] (4) The stirred kettle was sealed and the stirring speed was 50 rpm under the condition of uniform stirring. The vacuum degree of the kettle was 10 -3 Pa, so that the composite copper slurry is stirred and the bubbles inside the slurry are fully eliminated.

[0142] (5) Stop stirring, release the pressure, open the stirring kettle, and take out the finished composite copper slurry.

[0143] The composite copper paste prepared in Example 6 is applied to the surface of the HJT heterojunction cell by screen printing to form an electrode to be cured on the front side of the cell; wherein the printed paste has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 250°C for 5 minutes in air to cure the paste and form a metallized grid line.

[0144] Comparative Example 1

[0145] Commercially available nano copper paste 1 # , coated on the surface of the HJT heterojunction cell through a screen printing process to form an electrode to be cured on the front of the cell; wherein the printed slurry has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 195°C for 5 minutes in air conditions to cure the slurry and form a metallized grid line.

[0146] Among them, the nano copper paste 1 of comparative example 1 # In the invention, the particle size of the nano copper powder is 100 nm, and its mass proportion is 90%wt; the mass proportion of the organic carrier is 10%wt, and the organic carrier comprises epoxy resin, dibenzodisulfide, triethanolamine, oleic acid, and diethylene glycol butyl ether. Based on the weight of the organic carrier as 100%, the mass proportion of the epoxy resin is 55%, the mass proportion of dibenzodisulfide is 18%, the mass proportion of triethanolamine is 2%, the mass proportion of oleic acid is 3%, and the mass proportion of diethylene glycol butyl ether is 22%.

[0147] Comparative Example 2

[0148] Commercially available nano copper paste 2 # , coated on the surface of the HJT heterojunction cell through a screen printing process to form an electrode to be cured on the front of the cell; wherein the printed slurry has a thickness of 20 μm and a width of 50 μm; the printed cell is quickly baked at 250°C for 5 minutes in air conditions to cure the slurry and form a metallized grid line.

[0149] Among them, the nano copper paste 2 of comparative example 2 # In the invention, the particle size of the nano copper powder is 80 nm, and its mass proportion is 92%wt; the mass proportion of the organic carrier is 8%wt, and the organic carrier comprises epoxy resin, 2-hydroxyethyl disulfide, triethanolamine, oleic acid, diethylene glycol butyl ether, and pinene alcohol. Based on the weight of the organic carrier as 100%, the mass proportion of the epoxy resin is 60%, the mass proportion of 2-hydroxyethyl disulfide is 12%, the mass proportion of triethanolamine is 3%, the mass proportion of oleic acid is 3%, the mass proportion of diethylene glycol butyl ether is 10%, and the mass proportion of pinene alcohol is 12%.

[0150] Performance Testing

[0151] Porosity: The image analysis method was used to observe the cured grid lines through a scanning electron microscope (SEM), and the porosity was calculated using image analysis software.

[0152] Volume resistivity: The DC resistance method is used, which is a commonly used test method in the industry. A digital multimeter is used to measure the resistance of the cured gate line, and the volume resistivity is calculated based on the film thickness, resistance, and aspect ratio of the wiring pattern.

[0153] Table 1 Summary of performance test results of the composite copper paste prepared in the embodiment and the nano copper paste in the comparative example

[0154] Test subjects Porosity (%) Volume resistivity (μΩ·cm) Example 1 8.82 8.12 Example 2 8.91 8.39 Example 3 9.23 9.55 Example 4 9.18 9.46 Example 5 8.80 8.11 Example 6 8.76 8.09 Comparative Example 1 15.91 10.87 Comparative Example 2 10.26 10.01

[0155] Combined with Figure 1As can be seen from the data in Table 1, the metallized grid lines formed by the composite copper paste prepared by the preparation method of the present invention have low grid line porosity, high density and excellent conductivity. This is because in the process of heat curing, the active ingredients in the organic carrier will preferentially remove the existing oxide layer on the surface of the nano copper powder, and the resin in the carrier will isolate the copper powder surface from the air as a film-forming protective component to avoid further oxidation of the copper powder. Even if some copper powders are oxidized again, the remaining active ingredients can still remove the oxide. The tin alloy powder melts when reaching the curing temperature at the same time, and the molten liquid phase tin alloy fully infiltrates the gaps between the nano copper powders under the effect of the small size effect and the siphon effect of the nano copper powder, and the nano copper powder is wrapped in the tin alloy melt, and the tin melt will squeeze out the organic carrier in the gaps between the nano copper powders, because the density of the tin melt is close to the copper powder, and the carrier density is smaller, so the melt tends to separate from the organic component. In the temperature-lowering process, the tin melt cools and solidifies to form a composite grid line with the tin alloy as a matrix and the nano copper powder as a reinforcement. After adding the dispersant and curing agent, the dispersant can promote the full dispersion and more uniform mixing of powders of different sizes and between the powder and the organic carrier. The curing agent can promote faster film formation of the epoxy resin and protect the powder surface from oxidation. Therefore, the two will indirectly promote the reaction between the powder and the carrier, reduce the porosity of the gate line and increase the conductivity.

[0156] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A highly anti-oxidative composite copper paste, characterized in that: The composite copper slurry is formed by mixing the following raw materials: First conductive metal powder, second conductive metal powder, micron tin-based alloy powder and organic carrier; wherein, The first conductive metal powder is selected from at least one of nano silver powder and nano copper powder; The second conductive metal powder is selected from at least one of submicron copper powder and micron copper powder; The organic vehicle comprises a solvent, an active agent and a thermosetting resin.

2. The highly oxidation-resistant composite copper paste according to claim 1, characterized in that: The particle size of the first conductive metal powder is 50nm to 100nm; Preferably, the particle size of the second conductive metal powder is 100 nm to 1 μm, and the shape of the second conductive metal powder includes at least one of flake, spherical, and dendritic.

3. The highly oxidation-resistant composite copper paste according to claim 1, characterized in that: The particle size of the micron tin-based alloy powder is 2 μm to 15 μm; Preferably, the micron tin-based alloy powder is selected from one or more of tin-lead alloy powder, tin-lead-silver alloy powder, tin-lead-bismuth alloy powder, tin-copper alloy powder, tin-silver alloy powder, tin-silver-copper alloy powder, tin-bismuth alloy powder, tin-bismuth-silver alloy powder, and tin-antimony alloy powder.

4. The preparation method according to claim 1, characterized in that: Based on the total weight of all raw materials being 100%, the mass of the first conductive metal powder accounts for 10% to 20%, the mass of the second conductive metal powder accounts for 60% to 80%, the mass of the micron tin-based alloy powder accounts for 1% to 10%, and the mass of the organic carrier accounts for 10% to 20%.

5. The highly oxidation-resistant composite copper paste according to claim 1, characterized in that: Based on the total weight of the organic carrier as 100%, the mass percentage of the active agent is 3% to 5%; the mass percentage of the thermosetting resin is 25% to 55.5%; Preferably, the thermosetting resin is selected from one or more of epoxy resin, polyamide resin, saturated polyester resin, polyurethane resin, acrylic resin, and silicone resin; Preferably, the active agent is selected from one or more of citric acid, dibromosuccinic acid, stearic acid, succinic acid, salicylic acid, malonic acid, oxalic acid, glutaric acid, adipic acid, pimelic acid, azelaic acid, and sebacic acid; Preferably, the solvent is selected from one or more of octyl ether, tetrahydrofurfuryl alcohol, MPEG-250, MPEG-400, ethylene glycol methyl ether, ethylene glycol ethyl ether, polyethylene glycol 400, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, terpineol, 2,2,4-trimethyl 1,3-pentanediol diisobutyrate, and butyl acetate.

6. The highly oxidation-resistant composite copper paste according to claim 1, characterized in that: The organic carrier further comprises at least one of a curing agent, a surfactant, a dispersant and a thixotropic agent; Preferably, the curing agent is selected from at least one of organic amines and their derivatives, or selected from at least one of imidazoles and their derivatives; Preferably, the surfactant is selected from one or more of quaternary ammonium oleate, ammonium fluoroalkyl carboxylate, and dimethylamine hydrochloride; Preferably, the thixotropic agent is selected from one or more of castor oil, hydrogenated castor oil, and hardened castor oil; Preferably, the dispersant is selected from at least one of oleic acid, dodecyl mercaptan, sodium dodecyl sulfonate, and tetradecyltrimethylammonium bromide.

7. The highly oxidation-resistant composite copper paste according to claim 6, characterized in that: Based on the total weight of the organic carrier as 100%, the mass percentage of the curing agent is 5.5% to 20.5%; the mass percentage of the surfactant is 5% to 13%; the mass percentage of the dispersant is 3% to 7%; and the mass percentage of the thixotropic agent is 3% to 5%.

8. The highly oxidation-resistant composite copper paste according to claim 1, characterized in that: The curing temperature of the composite copper paste is 150° C. to 350° C., and the curing time is 5 min to 30 min.

9. A method for preparing the highly anti-oxidative composite copper paste according to any one of claims 1 to 8, characterized in that: The preparation method comprises: The first conductive metal powder and the second conductive metal powder are mixed with an organic carrier, and after being fully ground and dispersed, micron tin-based alloy powder is added and stirred evenly to obtain the composite copper slurry; Preferably, the stirring speed is 1 rpm to 100 rpm, and the stirring time is 10 min to 30 min; Preferably, the grinding is performed using a three-roll grinder, the roller spacing of which is 1 μm to 10 μm, and the number of times of grinding is 3 to 5 times.

10. The preparation method according to claim 9, characterized in that: The preparation method further comprises evacuating the composite copper slurry in a closed environment to remove bubbles inside the slurry; Preferably, the vacuum degree of the vacuum pumping is 10 -1 Pa~10 -5 Pa.

Citation Information

Patent Citations

  • Copper conductive slurry and preparation method and application thereof

    CN106981324A

  • Industrial low-temperature conductive paste with high conductivity and preparation method thereof

    CN115910423A

Cited By

  • Functional additive slurry, low-temperature curing copper slurry of N-type TOPCon solar cell, electrode and preparation method

    CN120936141A